Stowarzyszenie jako podmiot rozwoju lokalnego - Kańduła, Sławomira (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
In my opinion in Poland we do not attach great importance to activities of local associations. Whereas their activities have favourable influence on local development. The local associations spend money on education, cultural activities, physical education and sports. That organisations take care of environmental also. What is more, they help to obtain money for financing local development, for example from European Community. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1083, s. 269-277